2020
DOI: 10.1016/j.ebiom.2020.103076
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-omics reveal epigenomic disturbance of assisted reproductive technologies in human offspring

Abstract: Background The births of more than 8 million infants have been enabled globally through assisted reproductive technologies (ARTs), including conventional in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) with either fresh embryo transfer (ET) or frozen embryo transfer (FET). However, the safety issue regarding ARTs has drawn growing attention with accumulating observations of rising health risks, and underlying epigenetic mechanisms are largely uncharacterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 82 publications
(86 reference statements)
3
40
0
Order By: Relevance
“…Similar findings were recently reported by Chen and colleagues [24], who found that H3K4me3, but not H3K4me1, H3K27me3, or H3K27ac, showed differences in newborn CBMC from natural conception and ART groups. Herein, we found ICSI placentas showed lower levels of H3K4me3 than naturally conceived placentas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were recently reported by Chen and colleagues [24], who found that H3K4me3, but not H3K4me1, H3K27me3, or H3K27ac, showed differences in newborn CBMC from natural conception and ART groups. Herein, we found ICSI placentas showed lower levels of H3K4me3 than naturally conceived placentas.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, H3K4me3 is the most affected histone modification in the in vitro culture system [27]. A previous study suggested that H3K4me3 may potentially serve as a marker for evaluating the influence of ARTs [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, whilst there is evidence of ART affecting human birth weight [128] and associating with adverse cardiometabolic health in offspring [129][130][131], there are many confounders that complicate interpretation, including parental infertility status and varied demographics, the introduction of improved protocols over time and differences between clinics and the relatively young age of offspring born to date. Moreover, while epigenetic abnormalities are detected in ART offspring [132], variations in DNA methylation, potentially symptomatic of later disease, may not be permanent and can resolve by adulthood [133].…”
Section: From Diverse Peri-conception Environment To a Convergent Adult Disease Riskmentioning
confidence: 99%
“…Normalized normative adult peripheral blood RRBS profiles were obtained from GSE136849 (Table 1 ) ( 37 ). Because the RRBS dataset coordinates are based on the GRCh38/hg38 human genome assembly, they were converted to the GRCh37/hg19 assembly using liftover from the UCSC.…”
Section: Methodsmentioning
confidence: 99%
“…Predictors were tested on several independent blood-based datasets: normative samples from the GSE132203, GSE125105 and ARIES cohorts, as well as clinical and matching control samples from the Klinefelter (47,XXY), Turner (45,X) and 47,XXX syndrome cohorts ( 63–65 ). The region-based predictor was also tested in the blood RRBS dataset ( 37 ). All test results are presented in Table 3 .…”
Section: Methodsmentioning
confidence: 99%